Microbial Invasion vs. Tick Immune Regulation - Sonenshine, Daniel E.; Macaluso, Kevin R. (Frontiers in Cellular and Infection Microbiology, 2017)
Ticks transmit a greater variety of pathogenic agents that cause disease in humans and animals than any other haematophagous arthropod, including Lyme disease, Rocky Mountain spotted fever, human granulocytic anaplasmosis, babesiosis, tick-borne encephalitis, Crimean Congo haemorhagic fever, and many others (Gulia-Nuss et al., 2016). Although diverse explanations have been proposed to explain their remarkable vectorial capacity, among the most important are their blood feeding habit, their long term off-host survival, the diverse array of bioactive molecules that disrupt the host's natural hemostatic mechanisms, facilitate blood flow, pain inhibitors, and minimize inflammation to prevent immune rejection (Hajdušek et al., 2013). Moreover, the tick's unique intracellular digestive processes allow the midgut to provide a relatively permissive microenvironment for survival of invading microbes. Although tick-host-pathogen interactions have evolved over more than 300 million years (Barker and Murrell, 2008), few microbes have been able to overcome the tick's innate immune system, comprising both humoral and cellular processes that reject them. Similar to most eukaryotes, the signaling pathways that regulate the innate immune response, i.e., the Toll, IMD (Immunodeficiency) and JAK-STAT (Janus Kinase/ Signal Transducers and Activators of Transcription) also occur in ticks (Gulia-Nuss et al., 2016). Recognition of pathogen-associated molecular patterns (PAMPs) on the microbial surface triggers one or the other of these pathways. Consequently, ticks are able to mount an impressive array of humoral and cellular responses to microbial challenge, including anti-microbial peptides (AMPs), e.g., defensins, lysozymes, microplusins, etc., that directly kill, entrap or inhibit the invaders. Equally important are cellular processes, primarily phagocytosis, that capture, ingest, or encapsulate invading microbes, regulated by a primordial system of thioester-containing proteins, fibrinogen-related lectins and convertase factors (Hajdušek et al., 2013). Ticks also express reactive oxygen species (ROS) as well as glutathione-S-transferase, superoxide dismutase, heat shock proteins and even protease inhibitors that kill or inhibit microbes. Nevertheless, many tick-borne microorganisms are able to evade the tick's innate immune system and survive within the tick's body. The examples that follow describe some of the many different strategies that have evolved to enable ticks to transmit the agents of human and/or animal disease.